The development of an android-based SDQ application as an instrument to detect students’ psychological and behavioral problems - Irwandi Setiawan; Farida Aryani; Abdullah Sinring (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This study aims to determine the description of needs, produce a prototype, examine the validity, reliability, and practicality of an Android-based SDQ application as an instrument to detect students’ psychological and behavioral problems. This is an R&D study utilizing the Borg and Gall development model. Data was collected through observations, interviews, and questionnaires. Qualitative data was analyzed using content analysis, while quantitative data was analyzed using descriptive analysis. The results of the study showed that: 1) the development of an Android-based SDQ application to detect students’ psychological and behavioral problems is strongly needed by both school counselors and students; 2) the Android-based SDQ application prototype features menu items, school counselor profile, student profile, information on the objectives and advantages of SDQ, filling out SDQ, SDQ results, an application guidebook, SDQ statistical results, and an application management administrator; and 3) the Android-based SDQ application developed has been found to have high levels of validity, reliability, and practicality. Therefore, the Android-based SDQ application is considered a valid and reliable tool to detect students’ psychological and behavioral problems.